Oral hygiene habits and prosthodontic treatment needs in younger adolescent population of Pančevo, Serbia - Pavlovic, Maja; Jevremovic, Danimir; Matijevic, Dusanka; Vukovic, Branislava; Borotic, Nenad; Jevremovic, Ana; Tambur, Zoran; Lazic, Srdjan (Vojnosanitetski pregled, 2021)
Abstract Background/Aim. Dental status and oral hygiene habits are poor in young population living in deprived socioeconomic conditions. The aim of this research was to ascertain oral hygiene habits in adolescents attending high schools in urban area, determine the incidence of tooth loss at the age of 15–16 years and the gender difference. Methods. The epidemiological cross-sectional study included 234 randomly selected high school students. The research instruments were questionnaire (focusing on socio-demographic characteristics, habits, attitudes and behavior related to general and oral health) and clinical examination (tooth loss, normative need for prosthodontics restorations and presence of restorations). Results. Gender-related data comparison revealed that 32.5% of girls and 8.1% of boys had at least one tooth extracted (p < 0.05). Also, 56.2% of girls and 75.7% of boys brushed their teeth twice a day. Caries complications were identified as the indication for tooth extraction in 82.8% of participants. The data analysis confirmed the correlation between gender and tooth loss as well as treatment needs. Tooth loss was correlated with oral hygiene habits and reasons for dental visits. Treatment need was also affected by the reasons for tooth extraction and the absence of adequate prosthodontics therapy (p < 0.05). Conclusion. Sociodemographic conditions significantly influenced the number of participants with extracted teeth. A prosthodontic treatment need was influenced by the reasons for tooth extraction, adolescents’ knowledge about the importance of adequate treatment and previous unpleasant experience.